(untitled) (KULT_online, 2016)
Northwest Coast Representations: New Perspectives on History, Art, and Encounters, edited by Andreas Etges, Viola König, Rainer Hatoum, and Tina Brüderlin, provides deep insights into Northwest Coast artifacts, the aboriginal life, and their histories. This book offers a new perspective on different facets – including traditional narratives, language, and relations among these indigenous people – while depicting a number of (china) plates that tell the story of people there. Furthermore, this volume introduces the reader to the famous artists Doug Cranmer and ends with an informative summary of the history of the Northwest Coast art market.